Influence of inner meshing profile on noise of hybrid electric vehicles coupler chain based on vibration analysis - Lichi An; Gongfan Zhang (Scientific Reports)
Abstract Chain noise is an important factor affecting the ride comfort of hybrid electric vehicles (HEVs) with chain coupler. The inner meshing profile can effectively reduce the polygonal action, which has already been proved, but its influence on the noise is controversial. In this paper, the basic vibration locus, velocities, and acceleration for HEVs coupler chain are analyzed. Based on a specific example, under the action of the inner meshing profile, the indicators that represent the low, medium and high frequency vibration are proved to be reduced. Based on meshing relations, it is proved that the error of the inner meshing profile will cause the deviation of the chain pitch line and the meshing disorder, which may weaken the influence of inner meshing profile on reducing noise. Through conducting the dynamics simulation and the noise and wear experiment, the results show that the influence of the inner meshing profile on the noise has dual effect, and it can only reduce the noise after running-in. Moreover, under the action of the inner meshing profile, the noise level will be decreased with the increase of running time. This paper not only resolves the controversy but also provides an effective method for chain noise.